Emission pricing and CO₂ compensation in the EU: The optimal compensation to the power-intensive and trade-exposed industries for increased electricity prices - Kevin R. Kaushal; Lars Lindholt; Hidemichi Yonezawa (Statistics Norway, Research Department, 2023)
Unilateral CO2 emission reduction can lead to carbon leakage, such as relocation of power-intensive and trade-exposed industries. In the EU emission trading system, these industries are also subjected to higher cost of electricity due to emission pricing in this sector. As a result, the industries in the EU receive free emission allowances to mitigate carbon leakage as well as CO2 compensation due to higher electricity cost. This paper examines the welfare effects of supplementing free allowances with a CO2 compensation on the power-intensive and trade-exposed goods. The analytical results suggest that introducing CO2 compensation has a regional and global welfare improving effect under certain plausible conditions. Numerical simulations in the context of the EU ETS support the analytical findings if the emission reduction target is stringent enough.
Keywords: D61; F18; H23; Q54; 330; CO2 compensation; Emission trading system; Unilateral policy; Carbon leakage